Models as Make-Believe - Toon, Adam. author. aut Link
XVI, 148 p.
Keywords: Scientists often try to understand the world by building simplified and idealised models of it. Adam Toon develops a new approach to scientific models by comparing them to the dolls and toy trucks of children's imaginative games, and offers a unified framework to solve difficult metaphysical problems and help to make sense of scientific practice.